Fair evidence consistently supports open surgical treatment for chronic ankle instability: a systematic review. Issue 5 (26th September 2019) - Purcell, Chad Alexander; Calder, James; Matsui, Kentaro; Andersson, Pontus; Karlsson, Jón; ,; Glazebrook, Mark A
Abstract : Importance: Patients with chronic ankle instability (CAI) who have failed non-operative treatments are most commonly treated with open ankle repair or reconstruction of the anterior talofibular ligament and/or calcaneofibular ligament. Over 50 operative techniques have been described for the treatment of CAI. However, there is no current systematic evaluation of currently used open operative techniques for the treatment of CAI. Aim/Objective: The primary objective of this study is to provide evidence-based treatment recommendations for CAI in adults based on a comprehensive systematic review of the literature. Evidence review: The literature review of PubMed, EMBASE, Cochrane and Web of Science databases was completed on 22 February 2017. Search terms included two concepts: lateral ligament of the ankle (patients) and open reconstructive or repair procedures (intervention). All published clinical studies with English translation were included. Biomechanical, cadaveric, review articles, minimally invasive procedures and arthroscopic procedures were excluded. Open operative procedures from included articles were classified as anatomical or non-anatomical and repair or reconstructive. Articles were then assigned a level of evidence (I-V) to denote quality of the research methods. Articles were reviewed collectively to provide a grade of recommendation (A-C or I) in support for or against the operative intervention in treatment of CAI. Findings: Seventy one of 1635 identified articles were included for review. There is fair evidence (Grade B) in support of anatomical repair, anatomical reconstruction and non-anatomical reconstruction procedures. There was insufficient evidence available to grade internal brace and non-anatomical repair procedures. Conclusions and relevance: Although only fair-quality evidence exists in support of open operative treatment of CAI, this systematic review helps reassure clinicians of their current practices. The literature reaffirms support for open anatomical repair and anatomical reconstruction technique for CAI. Level of evidence: Level II, systematic review.